Karakteristik Kimia dan Penerimaan Selai Nangka (Artocarpus heterophyllus) dengan Variasi Penambahan Ekstrak Kayu Manis (Cinnamomum burmanni) - Sibuea, Budi Pratomo; Kholil, Munawar; Alghazali, Muntaha (Program Studi Teknologi Pangan, 2024)
Jam is a food product made from crushed fruit, with the addition of pectin and sugar to a gel or semi-solid consistency. Jackfruit, which bears fruit without knowing the season, is an excellent food source, but it spoils quickly and does not last long when stored. One way to use jackfruit is to make jam. It is hoped that the addition of cinnamon extract to making jackfruit jam will make jackfruit jam popular with all groups. The research used a Completely Randomized Design (CRD) with 3 treatments, namely the addition of cinnamon extract P1=15%, P2=25%, P3=35% with 3 replications. The jam will be analyzed for water content, vitamin C content and acceptance level based on color, aroma, texture and taste. The results of calculating the water content of jackfruit jam with the addition of cinnamon extract do not comply with theÂ SII NO. 173 Tahun 1978. Vitamin C levels are 1.13%, 1.25%, 1.42%. The results of the hedonic test analysis showed that the 25% cinnamon extract formulation was liked by the panelists based on taste, aroma and texture and really liked the color of the jam